Two-component polyurethane adhesive composition

By using a two-component system of NCO terminal blocking prepolymer and polyol and catalyst in polyurethane adhesive, combining aluminum hydroxide and alumina filler, the problem of insufficient working time of thermally conductive polyurethane adhesive is solved, and the battery module is realized The mechanical stability and thermal conductivity are improved, suitable for battery thermal management.

CN119137232APending Publication Date: 2024-12-13DUPONT TECH (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095726.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing thermally conductive polyurethane adhesives do not work enough during the bonding process of battery modules, which makes it difficult to meet the dual needs of thermal conductivity and mechanical stability, especially the problem of the adhesive curing too quickly during the bonding process that requires a long time.

Method used

Using a two-component polyurethane adhesive composed of NCO-capped prepolymer, polyol and catalyst, containing aluminum hydroxide and alumina filler, prepared by specific component ratios and reaction conditions, extending the working time of the adhesive and Improve its thermal conductivity.

Benefits of technology

It achieves extended working time of the adhesive and improved thermal conductivity, ensures the mechanical stability and thermal management performance of the battery module, and is suitable for efficient bonding between the battery and the cooling plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117399430000121
    Figure BDA0005117399430000121
  • Figure BDA0005117399430000241
    Figure BDA0005117399430000241
  • Figure BDA0005117399430000271
    Figure BDA0005117399430000271
Patent Text Reader

Abstract

A two component polyurethane adhesive composition is provided herein.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of two-component polyurethane adhesive compositions. Background Art

[0002] The demand for affordable, higher autonomous range electric vehicles has led to a rapid acceleration of innovation in electric vehicle (EV) battery concepts. During the past decade, higher energy density, lighter weight, higher durability and more economical EV battery concepts have been developed.

[0003] Innovation efforts are mainly focused in two directions: 1. Extending the autonomous range by increasing the energy packing density, and 2. Reducing the price of the battery. There are several strategies on the market to achieve a higher energy density of battery cells in order to reduce weight and increase the battery autonomy range, and all of them include thermal management concepts to optimize the operating conditions and life of the battery. Typical battery cells generate heat under standard operating conditions and during charging. The optimal operating temperature of the battery cell is between 25°C-40°C. The heat generated by the battery cell during operation is dissipated to the cooling plate. The battery cells or modules are connected to the cooling plate by thermally conductive materials. In order to improve the mechanical stability of the battery, a thermally conductive adhesive is required.

[0004] For the purpose of bonding battery modules, it is desirable that the adhesive have a fairly long working time. The working time is the time from when the components of the adhesive are mixed until the adhesive has cured sufficiently that the components of the bonded part can no longer move relative to each other. A long working time allows flexibility in the assembly process and, in the case of a thermally conductive adhesive, provides time for the adhesive to penetrate into a relatively small cavity and completely surround the battery component.

[0005] There remains a need for adhesives that are thermally conductive and show a working time greater than 30 minutes. Summary of the invention

[0006] In a first aspect, the present invention provides a two-component thermally conductive polyurethane adhesive comprising:

[0007] (A) Component A:

[0008] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0009] (B) Component B:

[0010] (bi) at least one polyol; and

[0011] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0012] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture.

[0013] In a second aspect, the present invention provides a kit for producing a thermally conductive polyurethane adhesive, comprising:

[0014] (A) Component A:

[0015] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0016] (B) Component B:

[0017] (bi) at least one polyol; and

[0018] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0019] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture.

[0020] In a third aspect, the present invention provides a method for bonding two or more substrates, the method comprising the steps of:

[0021] (1) Providing an adhesive, which comprises:

[0022] (A) Component A:

[0023] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0024] (B) Component B:

[0025] (bi) at least one polyol; and

[0026] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0027] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture;

[0028] (2) mixing component A and component B to produce an adhesive mixture;

[0029] (3) applying the adhesive mixture to a first substrate;

[0030] (4) bringing the first substrate into bonding contact with the second substrate;

[0031] (5) Allow the adhesive mixture to cure.

[0032] In a fourth aspect, the present invention provides a bonded assembly comprising:

[0033] (1) a first substrate;

[0034] (2) a second substrate bonded to the first substrate;

[0035] Wherein the first substrate and the second substrate are bonded to each other by an adhesive produced by mixing together the following component A and component B:

[0036] (A) Component A:

[0037] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0038] (B) Component B:

[0039] (bi) at least one polyol; and

[0040] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0041] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture. DETAILED DESCRIPTION

[0042] The inventors have found that by using a method comprising: n ) greater than 800Da and at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenyl isocyanate) (MDI) and 4,4'-MDI to make the isocyanate component of the prepolymer, and using a mixture of ATH and aluminum oxide as a filler, extended working time and slow compression force development in thermally conductive polyurethane adhesives can be achieved.

[0043] Definitions and Abbreviations

[0044] MDI Methylene-bis-(phenyl isocyanate)

[0045] HDI Hexamethylene diisocyanate

[0046] IPDI Isophorone diisocyanate

[0047] PU Polyurethane

[0048] GPC Gel Permeation Chromatography

[0049] RH Relative humidity

[0050] ATH Aluminum Hydroxide

[0051] Equivalent weight and molecular weight were measured by gel permeation chromatography (GPC) using a Malvern Viscothek GPC max device. Tetrahydrofuran (THF) was used as eluent, PL GEL MIXED D (Agilent, 300*7.5 mm, 5 μm) was used as a chromatographic column, and MALVERN Viscotek TDA (integrated refractive index viscometer and light scattering) was used as a detector.

[0052] The particle size of ATH was measured using laser diffraction with water containing 0.01 wt% sodium pyrophosphate as the suspension medium.

[0053] Component A (isocyanate)

[0054] Component A comprises at least one molecular weight (M n ) An NCO-terminated prepolymer prepared by reacting a polyether monool having a molecular weight greater than 800 Da with at least one polyisocyanate.

[0055] The polyether monool is preferably selected from poly(C 2-4 -alkylene oxide) glycol monoether, i.e. one of the terminal OH groups of the glycol is replaced by C 1-6 Ether group substitution, and poly (C 2-4 -Oxyalkylene) glycol monoesters, i.e. one of the terminal OH groups of the glycol is replaced by C 2-6 Ester group replacement.

[0056] In a preferred embodiment, the polyether monol is selected from the group consisting of monoethers of poly(ethylene oxide) glycol, monoethers of poly(propylene oxide) glycol, monoethers of poly(butylene oxide) glycol, and mixtures of these.

[0057] In a more preferred embodiment, the polyether monol is selected from monoethers of poly(propylene oxide) glycol.

[0058] Methyl, ethyl and propyl monoethers are preferred, with methyl ether being particularly preferred.

[0059] In a preferred embodiment, the polyether monol is selected from the monomethyl ether of poly(propylene oxide) glycol.

[0060] The polyether monol has a molecular weight (Mn) of greater than 800 Da and preferably less than 2,000 Da, more preferably less than 1,500 Da, very particularly preferably 1,000 Da.

[0061] In a preferred embodiment, the polyether monol is a poly(propylene oxide) diol, particularly one having a molecular weight (M) of 800-2,000 Da, more preferably 800-1,500 Da. n )'s monomethyl ether of poly(propylene glycol).

[0062] In a particularly preferred embodiment, the polyether monol is a poly(propylene oxide) diol, particularly having a molecular weight (M) of 1,000 Da. n )'s monomethyl ether of poly(propylene glycol).

[0063] The polyisocyanate is selected from aliphatic polyisocyanates and a mixture of 2,4'-MDI and 4,4'-MDI.

[0064] In a preferred embodiment, the polyisocyanate is aliphatic, with isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (HMDI) and hexamethylene diisocyanate (HDI) and mixtures of these being particularly preferred.

[0065] In another preferred embodiment, the polyisocyanate is a mixture of 2,4'-MDI and 4,4'-MDI. More preferably, the weight ratio of 2,4'-MDI to 4,4'-MDI is 0.667-1.5, more particularly preferably 0.8-1.5, even more particularly preferably 1-1.5.

[0066] Particularly preferred are mixtures of 2,4'-MDI and 4,4-MDI, wherein the weight ratio of 2,4'-MDI to 4,4-MDI is 1:1.

[0067] The NCO-terminated prepolymer of component A is prepared by reacting at least one polyether monool with at least one polyisocyanate. The reaction is preferably carried out under dry and inert conditions, in particular under vacuum. In a preferred embodiment, at least one polyether monool is first dried under vacuum and high temperature (>100° C.), and cooled (for example to 80° C.), and then at least one polyisocyanate is added under vacuum. The mixture is reacted under vacuum for 1-2 hours. The prepolymer (resulting reaction mixture) is used without purification.

[0068] At least one polyisocyanate is used in an amount such that there is an excess of NCO groups relative to the monool OH groups. In a preferred embodiment, at least one polyisocyanate is used in a stoichiometric excess of 2-15 times relative to the monool, more preferably 8-12 times relative to the monool, particularly preferably 10 times relative to the monool.

[0069] In a preferred embodiment, the prepolymer is made by reacting poly(propylene glycol) monomethyl ether with a mixture of 2,4'-MDI and 4,4'-MDI.

[0070] In another preferred embodiment, the prepolymer is prepared by making the molecular weight (M n )800-1,500Da poly(propylene glycol) monomethyl ether is reacted with a mixture of 2,4'-MDI and 4,4'-MDI.

[0071] At least one polyether monol is preferably used in component A in an amount of 5-20 wt %, more preferably 6-10 wt %, particularly preferably 8-9 wt %, based on the total weight of component A, it being understood that the polyether monol is in the form of a prepolymer.

[0072] The at least one polyisocyanate is preferably used in component A in an amount of 5 to 20 wt %, based on the total weight of component A, more preferably 6 to 15 wt %, very particularly preferably 10 to 11 wt %.

[0073] The NCO-terminated prepolymer is preferably produced with 30 to 55 wt %, more preferably 35 to 50 wt %, particularly preferably 42 to 45 wt %, of polyether monol, based on the total weight of the prepolymer.

[0074] The NCO-terminated prepolymers are preferably produced with 40 to 65 wt %, more preferably 45 to 60 wt %, particularly preferably 50 to 58 wt %, of diisocyanate, based on the total weight of the prepolymer.

[0075] In a preferred embodiment, the prepolymer is made with 30-55wt%, more preferably 35-50wt%, and particularly preferably 42-45wt% of a polyether monool based on the total weight of the prepolymer and 40-65wt%, more preferably 45-60wt%, and particularly preferably 50-58wt% of a diisocyanate based on the total weight of the prepolymer.

[0076] The prepolymer is preferably used in component A in an amount of 15 to 30 wt %, based on the total weight of component A, more preferably 16 to 25 wt %, very particularly preferably 18 to 20 wt %.

[0077] Component A may additionally comprise a silane comprising a 8-20 Examples of such silanes include trialkoxy-C 8-20 -alkylsilane, especially trimethoxy-C 8-20 -alkylsilane and triethoxy-C 8-20 -alkylsilane, wherein the trimethoxy-C 8-20 -Alkylsilanes are particularly preferred. In a preferred embodiment, component A comprises hexadecyl-trimethoxysilane.

[0078] If used, the silane is preferably present in component A at 0.25 to 3 wt %, based on the total weight of component A, more preferably 0.5 to 2 wt %, particularly preferably 0.75 to 1.2 wt %.

[0079] In a preferred embodiment, component A contains 0.25-3 wt %, more preferably 0.5-2 wt %, and particularly preferably 0.75-1.2 wt % of hexadecyltrimethoxysilane based on the total weight of component A.

[0080] Component A may additionally comprise ATH and alumina, as will be described in more detail below.

[0081] Component A may additionally comprise a fibrous filler such as wollastonite. If used, wollastonite is preferably present in an amount of 0.5-4 wt%, more preferably 1-3 wt%, very particularly preferably 1.7-2.2 wt%, based on the total weight of component A.

[0082] Component A may additionally comprise fumed silica. If used, fumed silica is preferably present in an amount of 0.75-2 wt%, more preferably 1-2 wt%, based on the total weight of component A.

[0083] Component A is typically formulated by drying solid ingredients (such as ATH and alumina, wollastonite, fumed silica) under vacuum at elevated temperature. Drying is preferably performed until the moisture content is 300 ppm or less. The prepolymer and silane (if used) are added to the dry ingredients and mixed to homogeneity under reduced pressure, and then component A is stored in a moisture-proof container.

[0084] Component B (polyol)

[0085] Component B comprises (bi) at least one polyol; and (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups.

[0086] The at least one polyol preferably comprises a polyol having a molecular weight less than 1,500 Da, more preferably less than or equal to 1,000 Da.

[0087] The at least one polyol preferably comprises diols, triols and mixtures of these. In a preferred embodiment, the at least one polyol comprises at least one diol, in particular a diol based on a polyether. In a particularly preferred embodiment, the at least one polyol comprises a diol based on poly(propylene oxide).

[0088] In a more preferred embodiment, the at least one polyol comprises a mixture of a diol and a triol.

[0089] In another preferred embodiment, the at least one polyol comprises diols, triols and mixtures of these, all of which have a molecular weight of less than 1,500 Da, more preferably less than 1,000 Da. In a preferred embodiment, the at least one polyol comprises a mixture of diols and triols, which have a molecular weight of less than 1,500 Da, more preferably less than 1,000 Da.

[0090] In a preferred embodiment, at least one polyol comprises a polyether polyol. Preferred polyether polyols are selected from poly(C 2-4 The polyols are preferably polyols based on poly(ethylene oxide), polyols based on poly(propylene oxide), polyols based on poly(butylene oxide) and mixtures of these. In a particularly preferred embodiment, the polyether polyols are selected from polyols based on poly(propylene oxide).

[0091] In another preferred embodiment, at least one polyol comprises a triol. The triol may be, for example, based on poly(C 2-4-alkylene oxide), in particular based on poly(propylene oxide), or it may be, for example, castor oil. In a particularly preferred embodiment, the triol is castor oil.

[0092] In a preferred embodiment, the at least one polyol comprises a mixture of polyether glycol and castor oil.

[0093] In another preferred embodiment, the at least one polyol comprises a mixture of a polyether glycol having a molecular weight of less than 600 Da and castor oil.

[0094] In another preferred embodiment, the at least one polyol comprises a mixture of a poly(propylene oxide)-based glycol and castor oil.

[0095] In another preferred embodiment, the at least one polyol comprises a mixture of a poly(propylene oxide)-based glycol having a molecular weight of less than 600 Da and castor oil.

[0096] In a preferred embodiment, component B comprises 2-15 wt %, more preferably 4-10 wt %, and very particularly preferably 5-7 wt %, of diol, based on the total weight of component B.

[0097] In another preferred embodiment, component B contains 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-11 wt %, of triol, based on the total weight of component B.

[0098] In another preferred embodiment, component B comprises 2-15 wt %, more preferably 4-10 wt %, very particularly preferably 5-7 wt %, based on the total weight of component B, of a diol having a molecular weight of less than 600 Da.

[0099] In another preferred embodiment, component B contains 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-11 wt %, based on the total weight of component B, of a triol having a molecular weight of less than 1,000 Da.

[0100] In another preferred embodiment, component B contains 2-15 wt%, more preferably 4-10 wt%, and more particularly preferably 5-7 wt%, of a diol having a molecular weight of less than 600 Da, based on the total weight of component B, and 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-11 wt%, of a triol having a molecular weight of less than 1,000 Da, based on the total weight of component B.

[0101] In another preferred embodiment, component B comprises 4-10 wt %, more particularly preferably 5-7 wt %, based on the total weight of component B, of poly(propylene oxide) glycol having a molecular weight of less than 600 Da.

[0102] In another preferred embodiment, component B contains 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-11 wt %, of castor oil, based on the total weight of component B.

[0103] In another preferred embodiment, component B comprises 4-10 wt %, more particularly preferably 5-7 wt %, of poly(propylene oxide) glycol having a molecular weight of less than 600 Da, based on the total weight of component B, and 5-20 wt %, more particularly preferably 7-15 wt %, particularly preferably 8-11 wt % of castor oil, based on the total weight of component B.

[0104] Component B additionally comprises a catalyst which is able to catalyze the reaction of isocyanate groups with OH groups.

[0105] Examples of such catalysts include tertiary amine catalysts, organic metal catalysts such as bismuth catalysts, alkyltin carboxylates, alkyltin oxides, and tin mercaptides.

[0106] Specific examples of tertiary amine catalysts include N-methylmorpholine, N-methylimidazole, triethylenediamine, bis-(2-dimethylaminoethyl)-ether, 1,4-diazabicyclo[2.2.2]octane (DABCO), dimethylcyclohexylamine, dimethylethanolamine, 2,2-dimorpholinyl-diethyl ether (DMDEE), N,N,N-dimethylaminopropylhexahydrotriazine, dimethyltetrahydropyrimidine, tetramethylethylenediamine, dimethylcyclohexylamine, 2,2-N,N-benzyldimethylamine, dimethylethanolamine, Amine, dimethylaminopropylamine, penta-dimethyldiethylenetriamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, N,N',N'-trimethylaminoethylpiperazine, 1,1'-[[3-(dimethylamino)propyl]imino]bispropan-2-ol, 1,3,5-tris[3-(dimethylamino)propyl]hexahydro-1,3,5-triazine, NN-dimethyldipropylenetriamine, N,N,N'-trimethylaminoethylethanolamine, among which DMDEE is particularly preferred.

[0107] If an organometallic catalyst is used, it is any organometallic catalyst capable of catalyzing the reaction of an isocyanate with a functional group having at least one reactive hydrogen. Examples include bismuth catalysts, metal carboxylates such as tin carboxylates and zinc carboxylates. Metal alkanoates include stannous octoate, bismuth octoate or bismuth neodecanoate. Preferably, at least one organometallic catalyst is a bismuth catalyst or an organotin catalyst. Examples include dibutyltin dilaurate, dimethyltin dineodecanoate, dimethyltin mercaptides, dimethyltin carboxylates, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin mercaptides, dibutyltin bis(2-ethylhexyl thioglycolate), dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin mercaptides, dioctyltin dioctoate, dioctyltin dineodecanoate, dioctyltin dilaurate. In a preferred embodiment, the catalyst is a tin catalyst, particularly preferably dioctyltin mercaptides and / or dimethyltin dithioglycolate. In a particularly preferred embodiment, the catalyst is dioctyltin mercaptides.

[0108] The catalyst is preferably used in an amount of 0.0005 to 0.002 wt %, based on the total weight of component B, more preferably 0.00075 to 0.0015 wt %.

[0109] In a preferred embodiment, the catalyst is dioctyltin mercaptan used at 0.0005 to 0.002 wt %, based on the total weight of component B, more preferably 0.00075 to 0.0015 wt %.

[0110] Component B may additionally comprise a silane comprising a 8-20 Examples of such silanes include trialkoxy-C 8-20 -alkylsilane, especially trimethoxy-C 8-20 -alkylsilane and triethoxy-C 8-20 -alkylsilane, wherein the trimethoxy-C 8-20 -Alkylsilanes are particularly preferred. In a preferred embodiment, component B comprises hexadecyl-trimethoxysilane.

[0111] If used, the silane is preferably present in component B in an amount of 0.25 to 3 wt %, based on the total weight of component B, more preferably 0.5 to 2 wt %, particularly preferably 0.75 to 1.2 wt %.

[0112] In a preferred embodiment, component B contains 0.25-3 wt %, more preferably 0.5-2 wt %, and particularly preferably 0.75-1.2 wt % of hexadecyltrimethoxysilane, based on the total weight of component B.

[0113] Component B may additionally comprise ATH and alumina, as will be described in more detail below.

[0114] Component B may additionally comprise a fibrous filler such as wollastonite. If used, wollastonite is preferably present in an amount of 0.75-5 wt %, based on the total weight of component B, more preferably 1-4 wt %, very particularly preferably 2.8-3.2 wt %.

[0115] Component B may additionally comprise fumed silica. If used, fumed silica is preferably present at 0.75-2 wt%, more preferably 1-2 wt%, based on the total weight of component A.

[0116] Component B may additionally comprise polyester diols. Examples include polycaprolactones, in particular having an average molecular weight (M) of 1,500 to 2,500 Da, more preferably 2,000 Da. n ) of polycaprolactone.

[0117] If used, the polyester diol is used at 0.1 to 0.4 wt %, based on the total weight of component B, more preferably 0.15 to 0.25 wt %.

[0118] Component B is typically formulated by drying solid ingredients (such as ATH and alumina, wollastonite, fumed silica) under vacuum at elevated temperature. Drying is preferably performed until the moisture content is 300 ppm or less. At least one polyol, catalyst, and silane (if used) are added to the dry ingredients and mixed to homogeneity under reduced pressure, and then component B is stored in a moisture-proof container.

[0119] filler

[0120] Component A and / or component B contains the following fillers:

[0121] Aluminium hydroxide (ATH) and alumina.

[0122] The ATH preferably has a multimodal particle size distribution. By expressing a multimodal particle size distribution is meant that if the particle size is plotted with particle size on the x-axis and volume % on the y-axis, at least two main peaks are observed.

[0123] In a preferred embodiment, the aluminum hydroxide is bimodal.

[0124] The particle size distribution of aluminum hydroxide is typically measured using laser diffraction, using water containing sodium pyrophosphate as a suspending agent.

[0125] In a preferred embodiment, the aluminum hydroxide has the following particle size distribution:

[0126] D 10 =0.5μm

[0127] D 50 =8μm

[0128] D 90 =80μm.

[0129] ATH is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form an adhesive mixture, the concentration of ATH in the adhesive mixture is at least 40 wt%, based on the total weight of the adhesive mixture. In a preferred embodiment, the concentration of ATH in the adhesive mixture is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of the adhesive mixture.

[0130] ATH may be present in component A, component B or both. Preferably, both component A and component B comprise ATH.

[0131] In a preferred embodiment, the concentration of ATH in component A is 40-65 wt %, more preferably 43-60 wt %, particularly preferably 44-57 wt %, based on the total weight of component A.

[0132] In a preferred embodiment, the concentration of ATH in component B is 40-65 wt %, more preferably 43-60 wt %, particularly preferably 44-57 wt %, based on the total weight of component B.

[0133] In a preferred embodiment, the concentration of ATH in component A is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of component A, and the concentration of ATH in component B is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of component B.

[0134] The alumina preferably has spherical particles.For the purpose of this specification, "spherical" means particles having an aspect ratio of 0.8-1.2, more preferably 0.9-1.1.

[0135] The alumina preferably has a multimodal particle size distribution.The expression multimodal particle size distribution means that if the particle size is plotted with particle size on the x-axis and volume % on the y-axis, at least two main peaks are observed.

[0136] Preferably, the alumina is bimodal.

[0137] The particle size distribution of alumina is typically measured using laser diffraction, using water containing sodium pyrophosphate as the suspending agent.

[0138] In a preferred embodiment, the alumina has the following particle size distribution:

[0139] D 10 =1-5μm, preferably 3μm

[0140] D 50=45-50μm, preferably 46.5μm

[0141] D 90 =80-100 μm, preferably 90 μm.

[0142] In a preferred embodiment, the alumina has the following particle size distribution:

[0143]

[0144] In a preferred embodiment, the aluminum oxide is a 5.7 μm D 50 of aluminum oxide and has a D of 72 μm 50 A mixture of aluminum oxides of 5.7 μm and 1.5 μm is particularly preferred. 50 of aluminum oxide and has a D of 72 μm 50 A mixture of 0.4:1 to 0.8:1, more preferably 0.5:1 to 0.7:1, particularly preferably 0.6:1 (wt:wt) of aluminum oxide.

[0145] Aluminum oxide is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form a binder mixture, the concentration of aluminum oxide in the binder mixture is at least 15 wt%, based on the total weight of the binder mixture. In a preferred embodiment, the concentration of aluminum oxide in the binder mixture is 15-40 wt%, more preferably 16-35 wt%, particularly preferably 17-34 wt%, based on the total weight of the binder mixture.

[0146] Alumina may be present in component A, component B or both. Preferably, both component A and component B comprise alumina.

[0147] In a preferred embodiment, the concentration of aluminum oxide in component A is 15-40 wt %, more preferably 16-35 wt %, particularly preferably 17-34 wt %, based on the total weight of component A.

[0148] In a preferred embodiment, the concentration of aluminum oxide in component B is 15-40 wt %, based on the total weight of component B, more preferably 16-35 wt %, particularly preferably 17-34 wt %.

[0149] In a preferred embodiment, the concentration of aluminum oxide in component A is 15-40wt%, more preferably 16-35wt%, and particularly preferably 17-34wt%, based on the total weight of component A, and the concentration of aluminum oxide in component B is 15-40wt%, more preferably 16-35wt%, and particularly preferably 17-34wt%, based on the total weight of component B.

[0150] In a preferred embodiment, ATH and alumina are multimodal.

[0151] In a preferred embodiment, ATH and alumina are bimodal.

[0152] In a preferred embodiment, the ATH and alumina are multimodal and the alumina has a spherical particle shape.

[0153] In a preferred embodiment, the ATH and alumina are bimodal and the alumina has a spherical particle shape.

[0154] In a preferred embodiment, the ATH has the following particle size distribution:

[0155] D 10 =0.5μm

[0156] D 50 =8μm

[0157] D 90 =80μm,

[0158] And the alumina has the following particle size distribution:

[0159] D 10 =1-5μm, preferably 3μm

[0160] D 50 =45-50μm, preferably 46.5μm

[0161] D 90 =80-100 μm, preferably 90 μm.

[0162] In a preferred embodiment, ATH is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form a binder mixture, the concentration of ATH in the binder mixture is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of the binder mixture, and the concentration of aluminum oxide in the binder mixture is 15-40 wt%, more preferably 16-35 wt%, particularly preferably 17-34 wt%, based on the total weight of the binder mixture.

[0163] In a preferred embodiment, ATH and alumina are present in both component A and component B.

[0164] In a preferred embodiment, the concentration of ATH in component A is 40-65wt%, more preferably 43-60wt%, particularly preferably 44-57wt%, based on the total weight of component A, and the concentration of aluminum oxide in component A is 15-40wt%, more preferably 16-35wt%, particularly preferably 17-34wt%, based on the total weight of component A.

[0165] In a preferred embodiment, the concentration of ATH in component B is 40-65wt%, more preferably 43-60wt%, particularly preferably 44-57wt%, based on the total weight of component B, and the concentration of aluminum oxide in component B is 15-40wt%, more preferably 16-35wt%, particularly preferably 17-34wt%, based on the total weight of component B.

[0166] In a preferred embodiment, the concentration of ATH in component A is 40-65wt%, more preferably 43-60wt%, and particularly preferably 44-57wt%, based on the total weight of component A, and the concentration of ATH in component B is 40-65wt%, more preferably 43-60wt%, and particularly preferably 44-57wt%, based on the total weight of component B, and the concentration of aluminum oxide in component A is 15-40wt%, more preferably 16-35wt%, and particularly preferably 17-34wt%, based on the total weight of component A, and the concentration of aluminum oxide in component B is 15-40wt%, more preferably 16-35wt%, and particularly preferably 17-34wt%, based on the total weight of component B.

[0167] Manufacturing method

[0168] The adhesive composition of the present invention is manufactured by mixing the ingredients of each component separately (preferably under inert and dry conditions and / or under vacuum) until a homogeneous mixture is obtained. Once the components are prepared, they are stored in separate containers until use.

[0169] How to use

[0170] In one aspect, the present invention provides a method for bonding two or more substrates, the method comprising the steps of:

[0171] (1) Providing an adhesive, which comprises:

[0172] (A) Component A:

[0173] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is produced by reacting a polyether monool having a molecular weight greater than 800 Da with at least one polyisocyanate;

[0174] (B) Component B:

[0175] (bi) at least one polyol; and

[0176] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0177] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture;

[0178] (2) mixing component A and component B to produce an adhesive mixture;

[0179] (3) applying the adhesive mixture to a first substrate;

[0180] (4) bringing the first substrate into bonding contact with the second substrate;

[0181] (5) Allow the adhesive mixture to cure.

[0182] The ingredients of components A and B which can be used in the process of the present invention are as described for the adhesive.

[0183] The mixing of component A and component B is carried out by any method that can achieve uniform mixing fairly quickly. Typically, the mixing is achieved by dispensing the two components simultaneously into a mixing container or channel. The mixing of component A and component B can be in any desired ratio, but typically uses a volume ratio of A:B of 0.8-1.2, more preferably 1.

[0184] Applying the adhesive mixture to the substrate is typically done using a suitable application gun and a static mixer. The adhesive is filled in a barrel, which ensures a suitable mixing ratio. The barrel is placed in an application gun and a suitable static mixer is installed. The adhesive is then pressed onto the surface to be bonded by the static mixer.

[0185] Curing is typically carried out at ambient temperature (eg 23°C) and humidity (eg 50% relative humidity).Full cure with the adhesive of the present invention is usually achieved within 7-10 days.

[0186] The substrate is not particularly limited and includes metals and plastics. The adhesive of the present invention is particularly suitable for bonding e-coated steel, PET film, aluminized plastic film, aluminum.

[0187] Preferred applications include thermally conductive materials for use in any application where a thermally conductive material is required, primarily in the automotive industry for thermal management of EV batteries; especially for bonding of modules or battery cells to cooling plates.

[0188] Effects of the Invention

[0189] The cured adhesive of the invention (7 days, 23° C., 50% RH) preferably shows a thermal conductivity of 1.5 W / mK or more, more preferably 1.6 W / mK or more, more particularly preferably 1.8 W / mK or more.The thermal conductivity is measured according to ASTM 5470, as described in the Examples.

[0190] When according to DIN EN 1465, the bonding area is: 250mm 2 (10 x 25 mm), 1 mm adhesive layer thickness, the cured adhesive of the present invention (7 days, 23° C., 50% RH) preferably exhibits a lap shear strength of 1.5 MPa or greater when measured using electro-coated steel for both substrates.

[0191] The adhesive mixture produced by mixing component A and component B (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) preferably has a working time of greater than 35 minutes, more preferably greater than 40 minutes, and particularly preferably greater than 50 minutes. When pressed into a 1 mm gap by parallel plates with a diameter of 50 mm at a pressing rate of 62.5 mm / min, the working time is the time to generate a compressive force of 150 kPa.

[0192] The adhesive mixture produced by mixing component A and component B (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) preferably has a compression force of less than 80 KPa, more preferably less than 78 KPa immediately after mixing when pressed by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min into a 1 mm gap.

[0193] The adhesive mixture produced by mixing component A and component B (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) preferably has a compression force of less than 130 KPa, more preferably less than 128 KPa 30 minutes after mixing when pressed by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min into a 1 mm gap.

[0194] The adhesive mixture resulting from mixing component A and component B (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) preferably has a compression force of less than 160 KPa, more preferably less than 155 KPa 60 minutes after mixing when pressed by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min into a 1 mm gap.

[0195] Particularly preferred embodiments

[0196] The following are particularly preferred embodiments of the adhesive composition of the present invention:

[0197] 1. A two-component thermally conductive polyurethane adhesive comprising:

[0198] (A) Component A:

[0199] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0200] (B) Component B:

[0201] (bi) at least one polyol; and

[0202] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0203] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture.

[0204] 2. A kit for producing a thermally conductive polyurethane adhesive, comprising:

[0205] (A) Component A:

[0206] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0207] (B) Component B:

[0208] (bi) at least one polyol; and

[0209] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0210] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture.

[0211] 3. A method for bonding two or more substrates, the method comprising the steps of:

[0212] (1) Providing an adhesive, which comprises:

[0213] (A) Component A:

[0214] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0215] (B) Component B:

[0216] (bi) at least one polyol; and

[0217] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0218] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture;

[0219] (2) mixing component A and component B to produce an adhesive mixture;

[0220] (3) applying the adhesive mixture to a first substrate;

[0221] (4) bringing the first substrate into bonding contact with the second substrate;

[0222] (5) The adhesive mixture is cured.

[0223] 4. A bonded assembly comprising:

[0224] (1) a first substrate;

[0225] (2) a second substrate bonded to the first substrate;

[0226] wherein the first substrate and the second substrate are bonded to each other by an adhesive produced by mixing together the following component A and component B:

[0227] (A) Component A:

[0228] (ai) an NCO-terminated prepolymer, the NCO-terminated prepolymer being obtained by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI;

[0229] (B) Component B:

[0230] (bi) at least one polyol; and

[0231] (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups;

[0232] wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture.

[0233] 5. As described in any of the preceding embodiments, wherein the polyether monool is selected from poly(C 2-4 -Oxyalkylene) glycol monoethers and poly(C 2-4 -monoesters of alkylene oxide) glycols.

[0234] 6. As described in any preceding embodiment, the polyether monol is selected from the group consisting of monoethers of poly(ethylene oxide) glycol, monoethers of poly(propylene oxide) glycol, monoethers of poly(butylene oxide) glycol, and mixtures thereof.

[0235] 7. As described in any of the preceding embodiments, the polyether monol is selected from monoethers of poly(propylene oxide) glycol.

[0236] 8. As described in any of the preceding embodiments, the polyether monol is selected from terminal methyl, ethyl and propyl monoethers.

[0237] 9. As described in any of the preceding embodiments, the polyether monool is selected from terminal methyl monoethers.

[0238] 10. As described in any of the preceding embodiments, the polyether monol is selected from the monomethyl ether of poly(propylene oxide) glycol.

[0239] 11. As described in any of the preceding embodiments, the polyether monol has a molecular weight (Mn) greater than 800 Da and less than 2,000 Da, more preferably less than 1,500 Da, and even more preferably 1,000 Da.

[0240] 12. As described in any of the preceding embodiments, wherein the polyether monol is a poly(propylene oxide) diol, particularly a poly(propylene oxide) diol having a molecular weight (M) of 1,000 Da. n )'s monomethyl ether of poly(propylene glycol).

[0241] 13. As described in any preceding embodiment, wherein the polyisocyanate is aliphatic.

[0242] 14. As described in any of the preceding embodiments, the polyisocyanate is selected from isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), and mixtures thereof.

[0243] 15. As described in any one of embodiments 1-12, wherein the polyisocyanate is a mixture of 2,4'-MDI and 4,4'-MDI.

[0244] 16. As described in any one of embodiments 1-12, wherein the polyisocyanate is a mixture of 2,4'-MDI and 4,4'-MDI, wherein the weight ratio of 2,4'-MDI to 4,4'-MDI is 0.667-1.5, more preferably 0.8-1.5, and more particularly preferably 1-1.5.

[0245] 17. As described in any one of embodiments 1-12, wherein the polyisocyanate used to make the prepolymer is a mixture of 4,4'-MDI and 2,4-MDI, wherein the weight ratio of 4,4'-MDI to 2,4-MDI is 1:1.

[0246] 18. As described in any of the preceding embodiments, the at least one polyisocyanate is used in a stoichiometric excess of 2-15 times relative to the monol, more preferably 8-12 times relative to the monol, particularly preferably 10 times relative to the monol.

[0247] 19. Any preceding embodiment wherein the prepolymer is made by reacting poly(propylene glycol) monomethyl ether with a mixture of 2,4'-MDI and 4,4'-MDI.

[0248] 20. As described in any of the preceding embodiments, wherein the prepolymer is prepared by making the molecular weight (Mn )800-1,500Da poly(propylene glycol) monomethyl ether is reacted with a mixture of 2,4'-MDI and 4,4'-MDI.

[0249] 21. As described in any of the preceding embodiments, the at least one polyether monol is used in component A in an amount of 5-20 wt %, more preferably 6-10 wt %, particularly preferably 8-9 wt %, based on the total weight of component A.

[0250] 22. As described in any of the preceding embodiments, the at least one polyisocyanate is used in component A in an amount of 5-20 wt %, more preferably 6-15 wt %, and more preferably 10-11 wt %, based on the total weight of component A.

[0251] 23. As described in any of the preceding embodiments, the NCO-terminated prepolymer comprises 30-55 wt%, more preferably 35-50 wt%, and particularly preferably 42-45 wt% of the polyether monol, based on the total weight of the prepolymer.

[0252] 24. As described in any of the preceding embodiments, the NCO-terminated prepolymer comprises 40-65 wt%, more preferably 45-60 wt%, and particularly preferably 50-58 wt% of diisocyanate based on the total weight of the prepolymer.

[0253] 25. As described in any of the preceding embodiments, the prepolymer comprises 30-55 wt%, more preferably 35-50 wt%, and particularly preferably 42-45 wt% of polyether monool, based on the total weight of the prepolymer, and 40-65 wt%, more preferably 45-60 wt%, and particularly preferably 50-58 wt% of diisocyanate, based on the total weight of the prepolymer.

[0254] 26. As described in any of the preceding embodiments, the prepolymer is used in component A at 15-30 wt%, more preferably 16-25 wt%, and more preferably 18-20 wt%, based on the total weight of component A.

[0255] 27. As described in any of the preceding embodiments, wherein component A and / or component B additionally comprises a silane comprising a silane covalently bonded to C 8-20 A hydrolyzable silylalkoxy group of an alkyl group.

[0256] 28. As described in any preceding embodiment, component A and / or component B comprises hexadecyl-trimethoxysilane.

[0257] 29. As described in any of the preceding embodiments, component A and / or component B contains 0.25-3 wt %, more preferably 0.5-2 wt %, and particularly preferably 0.75-1.2 wt % of silane based on the total weight of component A or component B.

[0258] 30. As described in any preceding embodiment, wherein component A and / or component B additionally comprises a fibrous filler, such as wollastonite.

[0259] 31. As described in any of the preceding embodiments, component A and / or component B comprises 0.5-4 wt%, more preferably 1-3 wt%, and more preferably 1.7-2.2 wt% of wollastonite based on the total weight of component A or component B.

[0260] 32. As described in any preceding embodiment, wherein the at least one polyol comprises a polyol having a molecular weight less than 1,500 Da, more preferably less than or equal to 1,000 Da.

[0261] 33. As described in any preceding embodiment, wherein the at least one polyol comprises diols, triols, and mixtures thereof.

[0262] 34. As described in any of the preceding embodiments, wherein the at least one polyol includes at least one diol, in particular a polyether-based diol.

[0263] 35. As described in any preceding embodiment, wherein the at least one polyol comprises a poly(propylene oxide)-based diol.

[0264] 36. Any preceding embodiment, wherein the at least one polyol comprises a mixture of diols and triols.

[0265] 37. As described in any preceding embodiment, wherein the at least one polyol includes diols, triols, and mixtures of these, all of which have a molecular weight of less than 1,500 Da, more preferably less than 1,000 Da.

[0266] 38. As described in any preceding embodiment, the at least one polyol comprises a mixture of diols and triols having a molecular weight of less than 1,500 Da, more preferably less than 1,000 Da.

[0267] 39. As described in any preceding embodiment, wherein the at least one polyol comprises a polyether polyol.

[0268] 40. As described in any of the preceding embodiments, wherein the at least one polyol comprises a polyether polyol selected from the group consisting of: poly(C 2-4

[0043] Polyols based on poly(ethylene oxide), polyols based on poly(propylene oxide), polyols based on poly(butylene oxide) and mixtures of these.

[0269] 41. As described in any preceding embodiment, the at least one polyol is selected from poly(propylene oxide)-based polyols.

[0270] 42. As described in any preceding embodiment, wherein the at least one polyol comprises a triol.

[0271] 43. As described in any of the preceding embodiments, wherein the at least one polyol comprises a polyol selected from the group consisting of 2-4 -alkylene oxide) triol.

[0272] 44. Any preceding embodiment, wherein the at least one polyol comprises a poly(propylene oxide)-based triol.

[0273] 45. As described in any preceding embodiment, wherein the at least one polyol includes castor oil.

[0274] 46. ​​Any preceding embodiment, wherein the at least one polyol comprises a mixture of polyether glycol and castor oil.

[0275] 47. As described in any preceding embodiment, the at least one polyol comprises a mixture of a polyether glycol having a molecular weight of less than 600 Da and castor oil.

[0276] 48. Any preceding embodiment, wherein the at least one polyol comprises a mixture of a poly(propylene oxide)-based glycol and castor oil.

[0277] 49. Any preceding embodiment, wherein the at least one polyol comprises a mixture of a poly(propylene oxide)-based glycol having a molecular weight of less than 600 Da and castor oil.

[0278] 50. As described in any of the preceding embodiments, wherein component B comprises 2-15 wt %, more preferably 4-10 wt %, and even more preferably 5-7 wt % of diol based on the total weight of component B.

[0279] 51. As described in any of the preceding embodiments, component B comprises 5-20 wt %, more preferably 7-15 wt %, and particularly preferably 8-11 wt % of triol based on the total weight of component B.

[0280] 52. As described in any of the preceding embodiments, component B comprises 2-15 wt%, more preferably 4-10 wt%, and more preferably 5-7 wt%, based on the total weight of component B, of a diol having a molecular weight of less than 600 Da.

[0281] 53. As described in any of the preceding embodiments, wherein component B comprises 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-11 wt%, based on the total weight of component B, of a triol having a molecular weight of less than 1,000 Da.

[0282] 54. As described in any of the preceding embodiments, component B comprises 2-15 wt%, more preferably 4-10 wt%, and more particularly preferably 5-7 wt%, of a diol having a molecular weight of less than 600 Da, based on the total weight of component B, and 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-11 wt%, of a triol having a molecular weight of less than 1,000 Da, based on the total weight of component B.

[0283] 55. As described in any of the preceding embodiments, component B comprises 4-10 wt%, more preferably 5-7 wt%, based on the total weight of component B, of a poly(propylene oxide) glycol having a molecular weight of less than 600 Da.

[0284] 56. As described in any of the preceding embodiments, component B comprises 5-20 wt %, more preferably 7-15 wt %, and particularly preferably 8-11 wt % of castor oil based on the total weight of component B.

[0285] 57. As described in any of the preceding embodiments, component B comprises 4-10 wt%, more preferably 5-7 wt%, of poly(propylene oxide) glycol having a molecular weight of less than 600 Da, based on the total weight of component B, and 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-11 wt% of castor oil, based on the total weight of component B.

[0286] 58. As described in any preceding embodiment, the catalyst is selected from tertiary amine catalysts and organometallic catalysts.

[0287] 59. As described in any preceding embodiment, wherein the catalyst is selected from alkyl tin carboxylates, alkyl tin oxides, and tin mercaptides.

[0288] 60. Any preceding embodiment, wherein the catalyst is dioctyltin mercaptan.

[0289] 61. As described in any of the preceding embodiments, wherein the catalyst is used in an amount of 0.0005 to 0.002 wt%, more preferably 0.00075 to 0.0015 wt%, based on the total weight of component B.

[0290] 62. As described in any preceding embodiment, wherein the catalyst is dioctyltin mercaptan used at 0.0005 to 0.002 wt%, more preferably 0.00075 to 0.0015 wt%, based on the total weight of component B.

[0291] 63. Any preceding embodiment wherein component B additionally comprises a polyester diol.

[0292] 64. Any preceding embodiment wherein component B additionally comprises polycaprolactone.

[0293] 65. As described in any of the preceding embodiments, wherein component B additionally comprises an average molecular weight (M) of 1,500-2,500 Da, more preferably 2,000 Da. n ) of polycaprolactone.

[0294] 66. As described in any preceding embodiment, wherein component B additionally comprises a polyester diol used in an amount of 0.1-0.4 wt %, more preferably 0.15-0.25 wt %, based on the total weight of component B.

[0295] 67. As described in any preceding embodiment, wherein the ATH has a multimodal particle size distribution.

[0296] 68. As described in any preceding embodiment, wherein the ATH has a bimodal particle size distribution.

[0297] 69. As described in any of the preceding embodiments, wherein the aluminum hydroxide has the following particle size distribution:

[0298] D 10 =0.5μm

[0299] D 50 =8μm

[0300] D 90 =80μm.

[0301] 70. As described in any of the preceding embodiments, ATH is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form an adhesive mixture, the concentration of ATH in the adhesive mixture is 40-65 wt%, more preferably 43-60 wt%, and particularly preferably 44-57 wt%, based on the total weight of the adhesive mixture.

[0302] 71. Any preceding embodiment, wherein ATH is present in Component A, Component B, or both.

[0303] 72. As described in any preceding embodiment, wherein both component A and component B comprise ATH.

[0304] 73. As described in any of the preceding embodiments, the concentration of ATH in component A is 40-65 wt%, more preferably 43-60 wt%, and particularly preferably 44-57 wt%, based on the total weight of component A.

[0305] 74. As described in any of the preceding embodiments, the concentration of ATH in component B is 40-65 wt%, more preferably 43-60 wt%, and particularly preferably 44-57 wt%, based on the total weight of component B.

[0306] 75. As described in any of the preceding embodiments, the concentration of ATH in component A is 40-65 wt%, more preferably 43-60 wt%, and particularly preferably 44-57 wt%, based on the total weight of component A, and the concentration of ATH in component B is 40-65 wt%, more preferably 43-60 wt%, and particularly preferably 44-57 wt%, based on the total weight of component B.

[0307] 76. As described in any preceding embodiment, the aluminum oxide has spherical particles.

[0308] 77. As described in any of the preceding embodiments, the aluminum oxide particles have an aspect ratio of 0.8-1.2, more preferably 0.9-1.1.

[0309] 78. As described in any preceding embodiment, the aluminum oxide has a multimodal particle size distribution.

[0310] 79. As described in any preceding embodiment, wherein the alumina is bimodal.

[0311] 80. As described in any preceding embodiment, the aluminum oxide has the following particle size distribution:

[0312] D 10 =1-5μm, preferably 3μm

[0313] D 50 =45-50μm, preferably 46.5μm

[0314] D 90 =80-100 μm, preferably 90 μm

[0315] 81. As described in any preceding embodiment, the aluminum oxide has the following particle size distribution:

[0316]

[0317] 82. As described in any of the preceding embodiments, the aluminum oxide has a D 50 of aluminum oxide and has a D of 72 μm 50 A mixture of aluminum oxide.

[0318] 83. As described in any of the preceding embodiments, the aluminum oxide has a D 50 of aluminum oxide and has a D of 72 μm 50 A mixture of 0.4:1 to 0.8:1, more preferably 0.5:1 to 0.7:1, particularly preferably 0.6:1 (wt:wt) of aluminum oxide.

[0319] 84. As described in any of the preceding embodiments, the aluminum oxide is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form a binder mixture, the concentration of aluminum oxide in the binder mixture is 15-40 wt%, more preferably 16-35 wt%, and particularly preferably 17-34 wt%, based on the total weight of the binder mixture.

[0320] 85. As described in any preceding embodiment, wherein the aluminum oxide is present in component A, component B, or both.

[0321] 86. As described in any preceding embodiment, wherein both component A and component B comprise aluminum oxide.

[0322] 87. As described in any of the preceding embodiments, the concentration of aluminum oxide in component A and / or B is 15-40 wt%, more preferably 16-35 wt%, and particularly preferably 17-34 wt%, based on the total weight of component A or B.

[0323] 88. As described in any preceding embodiment, wherein the ATH and the alumina are multimodal.

[0324] 89. As described in any preceding embodiment, wherein the ATH and the alumina are bimodal.

[0325] 90. As described in any preceding embodiment, wherein the ATH and the alumina are multimodal, and the alumina has a spherical particle shape.

[0326] 91. As described in any preceding embodiment, the ATH and the alumina are multimodal, and the alumina has an aspect ratio of 0.8-1.2, more preferably 0.9-1.1.

[0327] 92. As described in any preceding embodiment, wherein the ATH and the alumina are bimodal, and the alumina has a spherical particle shape.

[0328] 93. As described in any preceding embodiment, the ATH and the alumina are bimodal, and the alumina has an aspect ratio of 0.8-1.2, more preferably 0.9-1.1.

[0329] 94. As described in any preceding embodiment, wherein the ATH has the following particle size distribution:

[0330] D 10 =0.5μm

[0331] D 50 =8μm

[0332] D 90 =80μm,

[0333] And the alumina has the following particle size distribution:

[0334] D 10 =1-5μm, preferably 3μm

[0335] D 50 =45-50μm, preferably 46.5μm

[0336] D 90 =80-100 μm, preferably 90 μm

[0337] 95. As described in any preceding embodiment, the ATH is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form a binder mixture, the concentration of ATH in the binder mixture is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of the binder mixture, and the concentration of aluminum oxide in the binder mixture is 15-40 wt%, more preferably 16-35 wt%, particularly preferably 17-34 wt%, based on the total weight of the binder mixture.

[0338] 96. As described in any preceding embodiment, wherein ATH and alumina are both present in component A and component B.

[0339] 97. As described in any of the preceding embodiments, the concentration of ATH in component A is 40-65wt%, more preferably 43-60wt%, and particularly preferably 44-57wt%, based on the total weight of component A, and the concentration of alumina in component A is 15-40wt%, more preferably 16-35wt%, and particularly preferably 17-34wt%, based on the total weight of component A.

[0340] 98. As described in any of the preceding embodiments, the concentration of ATH in component B is 40-65 wt%, more preferably 43-60 wt%, and particularly preferably 44-57 wt%, based on the total weight of component B, and the concentration of alumina in component B is 15-40 wt%, more preferably 16-35 wt%, and particularly preferably 17-34 wt%, based on the total weight of component B.

[0341] 99. As described in any of the preceding embodiments, the concentration of ATH in component A is 40-65wt%, more preferably 43-60wt%, and particularly preferably 44-57wt%, based on the total weight of component A, and the concentration of ATH in component B is 40-65wt%, more preferably 43-60wt%, and particularly preferably 44-57wt%, based on the total weight of component B, and the concentration of aluminum oxide in component A is 15-40wt%, more preferably 16-35wt%, and particularly preferably 17-34wt%, based on the total weight of component A, and the concentration of aluminum oxide in component B is 15-40wt%, more preferably 16-35wt%, and particularly preferably 17-34wt%, based on the total weight of component B.

[0342] 100. As described in any of the preceding embodiments, component A and component B are mixed in a volume ratio of A:B of 0.8-1.2.

[0343] 101. As described in any of the preceding embodiments, component A and component B are mixed in a volume ratio of A:B of 1.

[0344] 102. As described in any of the preceding embodiments, wherein, as described in the example, the adhesive shows a thermal conductivity of 1.5 W / mK or greater, more preferably 1.6 W / mK or greater, and more particularly preferably 1.8 W / mK or greater after curing for seven days at 23°C and 50% relative humidity when measured according to ASTM 5470.

[0345] 103. As in any preceding embodiment, wherein, when in accordance with DIN EN 1465, the bonding area is: 250 mm 2 (10 x 25 mm), an adhesive layer thickness of 1 mm, the adhesive showed a lap shear strength of 1.5 MPa or greater after curing for seven days at 23°C and 50% relative humidity when measured using electro-coated steel for both substrates.

[0346] 104. As described in any of the aforementioned embodiments, wherein the adhesive mixture produced by mixing component A and component B has a working time greater than 35 minutes, more preferably greater than 40 minutes, and particularly preferably greater than 50 minutes, wherein the working time is the time to generate a compressive force of 150 KPa when pressed into a 1 mm gap by parallel plates with a diameter of 50 mm at a pressing rate of 62.5 mm / min.

[0347] 105. As described in any of the preceding embodiments, wherein the adhesive mixture produced by mixing component A and component B has a compression force of less than 80 KPa, more preferably less than 78 KPa, immediately after mixing when pressed into a 1 mm gap by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min.

[0348] 106. As described in any of the preceding embodiments, wherein the adhesive mixture produced by mixing component A and component B has a compression force of less than 130 KPa, more preferably less than 128 KPa 30 minutes after mixing when pressed into a 1 mm gap by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min.

[0349] 107. As described in any of the preceding embodiments, wherein the adhesive mixture produced by mixing component A and component B has a compression force of less than 160 KPa, more preferably less than 155 KPa 60 minutes after mixing when pressed into a 1 mm gap by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min.

[0350] Examples

[0351]

[0352]

[0353] Preparation of adhesives

[0354] Component A (isocyanate)

[0355] Prepolymer preparation

[0356] The prepolymer was prepared in a 21 four-necked flask equipped with a mechanical stirring rod and a thermometer. The isocyanate-terminated prepolymer was prepared by first mixing the monool or polyol components of component A (DONOL 1000 or NJ-330) and stirring at 120°C for 1 hour under reduced pressure. The polyol was cooled to 80°C, and MDI-50 was added, and the mixture was reacted at 80°C for 2 hours under reduced pressure. The material was then cooled to less than 30°C. The vacuum was broken under nitrogen, and the prepolymer was stored airtight until use.

[0357] Inventive Example 5 provides a detailed description of the prepolymer process. At room temperature, 422 g of DONOL 1000 was added to a four-necked flask equipped with a mechanical stirring rod and a thermometer. DONOL 1000 was dried at 120° C. for 1 hour under reduced pressure. DONOL 1000 was cooled to 80° C. and 528 g of MDI-50 was added to the flask, and the mixture was reacted at 80° C. for 2 hours under reduced pressure. The material was cooled to less than 30° C. The vacuum was broken under nitrogen, and the prepolymer was stored airtight until use. The prepolymer was prepared with an excess of isocyanate, resulting in a prepolymer that was primarily NCO-terminated.

[0358] In order to prepare component A, using the amount listed in Table 2, Apyral 20X, SA0050, SA0700, WP2500 and CAB-O-SIL TS-720 are dried in an oven at 120 ℃ for 24 hours or longer, until the moisture content is less than 300ppm. Prepolymer, Dynasylan 9116, JSLD4529 and PTSI are added in a 2l planetary mixer and mixed together for 10 minutes. Add Apyral 20X, CAB-O-SIL TS-720 and WP2500, and continue to stir for another 30 minutes at room temperature. Add SA0050 and SA0700, and continue to stir for an additional 30 minutes under reduced pressure. Then break the vacuum under nitrogen, and component A is packaged in an airtight cartridge for storage until use.

[0359] Example 5 of the present invention provides a specific description of the preparation of component A. Solid Apyral 20X, SA0050, S0700, WP2500 and CAB-O-SIL TS-720 were dried in a 120°C oven for at least 24 hours until the moisture content was less than 300ppm. 190g of prepolymer, 10g of Dynasylan 9116, 1g of JSLD4529 and 5g of PTSI were added to a 2L planetary mixer laboratory scale mixer. After mixing for 10 minutes, 561g of Apyral 20X, 13g of CAB-O-SIL TS-720 and 20g of WP2500 were added to the mixer. Stirring was maintained at room temperature for half an hour, and then, 75g of SA0050, 125g of SA0700 were added. The mixture was kept stirring at room temperature for another half an hour under reduced pressure. Finally, the vacuum was broken with nitrogen, and the adhesive component can be filled in a suitable packaging size.

[0360] Component B (polyol)

[0361] To prepare component B (polyol), the solid ingredients Apyral 20X, SA0050, SA0700, WP2500 and CAB-O-SIL TS-720 were dried in an oven at 120°C for 24 hours or longer, until the moisture content was less than 300ppm, using the amounts listed in Table 2. Liquid polyols (NJ-204 and castor oil) were dried using molecular sieves, until the moisture content was less than 300ppm. CAPA 2201 and Dynasylan 9116 were added along with the dried solid ingredients, and stirring was continued for 30 minutes. Molecular sieves and Fomrez UL-29 were added and stirring was continued for another 30 minutes. The vacuum was broken under nitrogen, and component B was filled in an airtight cartridge until use.

[0362] Components A and B were stored separately until use. The components were mixed in a 1:1 volume ratio immediately before use and the following tests were performed.

[0363] Working hours

[0364] The time after mixing to generate a compressive force of 150 KPa. The results are listed in Table 2.

[0365] Compression force

[0366] 10g of adhesive produced by mixing component A and B in a volume ratio of 1:1 is pressed into a 1mm gap by a parallel plate with a diameter of 50mm at a compression rate of 62.5mm / min. Required force is reported as the compression force in KPa. Measure immediately after mixing ("initial") and measure the compression force after having passed 15, 30 and 60 minutes ("open time"). The results are listed in Table 2.

[0367] Lap shear strength

[0368] Lap shear strength using DIN EN 1465, bond area: 250mm 2 (10×25 mm), 1 mm adhesive layer thickness, measured using electro-coated steel for both substrates. All surfaces were prepared by cleaning with isopropyl alcohol before applying the adhesive. Curing conditions were 7 days at 23° C. at 50% RH. Shear samples were pulled at 5 mm / min during testing.

[0369] Thermal conductivity

[0370] Thermal conductivity was measured according to ASTM D5470. Testing was performed using a thermal interface material tester from Linseis TIM D5470. After curing for 7 days at 23°C and 50% RH, measurements were performed in Spaltplus mode at adhesive thicknesses between 1.5-3.0 mm. The absolute thermal conductivity λ (W / mK) was recorded. The results are listed in Table 2.

[0371]

[0372] result

[0373] Inventive Examples 5 and 6 both showed working times significantly greater than 35 minutes (60 minutes and >60 minutes, respectively), while the Comparative Examples showed working times of 30 minutes or less.

[0374] Inventive Examples 5 and 6 showed an initial compression force that was significantly less than the comparative example, and this was also true at 15, 30 and 60 minutes open time (time after mixing).

[0375] Inventive Examples 5 and 6 also show better thermal conductivity (≥2 W / mK) than the comparative examples (≥1.8 W / mK).

Claims

1. A two-component thermally conductive polyurethane adhesive comprising: (A) Component A: (ai) an NCO-terminated prepolymer, wherein the NCO-terminated prepolymer is prepared by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI; (B) Component B: (bi) at least one polyol; and (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups; wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce an adhesive mixture, the content of ATH in the adhesive mixture is at least 40 wt %, based on the total weight of the adhesive mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce an adhesive mixture, the content of aluminum oxide in the adhesive mixture is at least 15 wt %, based on the total weight of the adhesive mixture.

2. A kit for producing a thermally conductive polyurethane adhesive, comprising: (A) Component A: (ai) an NCO-terminated prepolymer, wherein the NCO-terminated prepolymer is prepared by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI; (B) Component B: (bi) at least one polyol; and (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups; wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce an adhesive mixture, the content of ATH in the adhesive mixture is at least 40 wt %, based on the total weight of the adhesive mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce an adhesive mixture, the content of aluminum oxide in the adhesive mixture is at least 15 wt %, based on the total weight of the adhesive mixture.

3. A method for bonding two or more substrates, the method comprising the steps of: (1) Providing an adhesive, which comprises: (A) Component A: (ai) an NCO-terminated prepolymer, wherein the NCO-terminated prepolymer is prepared by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI; (B) Component B: (bi) at least one polyol; and (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups; wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce a binder mixture, the content of ATH in the binder mixture is at least 40 wt %, based on the total weight of the binder mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce a binder mixture, the content of aluminum oxide in the binder mixture is at least 15 wt %, based on the total weight of the binder mixture; (2) mixing component A and component B to produce an adhesive mixture; (3) applying the adhesive mixture to a first substrate; (4) bringing the first substrate into bonding contact with the second substrate; (5) Curing the adhesive mixture.

4. A bonded assembly comprising: (1) a first substrate; (2) a second substrate bonded to the first substrate; wherein the first substrate and the second substrate are bonded to each other by an adhesive produced by mixing together the following component A and component B: (A) Component A: (ai) an NCO-terminated prepolymer, wherein the NCO-terminated prepolymer is prepared by making at least one molecular weight (M n ) is prepared by reacting a polyether monool having a Da of greater than 800 with at least one polyisocyanate selected from aliphatic polyisocyanates and a mixture of 2,4'-methylene-bis-(phenylisocyanate) (MDI) and 4,4'-MDI; (B) Component B: (bi) at least one polyol; and (bii) a catalyst capable of catalyzing the reaction of OH groups with NCO groups; wherein component A and / or component B comprises aluminum hydroxide (ATH) in an amount such that when components A and B are mixed to produce an adhesive mixture, the content of ATH in the adhesive mixture is at least 40 wt %, based on the total weight of the adhesive mixture, and wherein component A and / or component B comprises aluminum oxide in an amount such that when components A and B are mixed to produce an adhesive mixture, the content of aluminum oxide in the adhesive mixture is at least 15 wt %, based on the total weight of the adhesive mixture.

5. A method as claimed in any preceding claim, wherein: The polyether monool is selected from poly(C 2-4 -Oxyalkylene) glycol monoethers and poly(C 2-4 -monoesters of alkylene oxide) glycols.

6. A method as claimed in any preceding claim, wherein: The polyether monol is selected from the group consisting of monoethers of poly(ethylene oxide) glycol, monoethers of poly(propylene oxide) glycol, monoethers of poly(butylene oxide) glycol, and mixtures of these.

7. A method as claimed in any preceding claim, wherein: The polyether monol is selected from monoethers of poly(propylene oxide) glycol.

8. A method as claimed in any preceding claim, wherein: The polyether monol is selected from terminal methyl, ethyl and propyl monoethers.

9. A method as claimed in any preceding claim, wherein: The polyether monool is selected from terminal methyl monoethers.

10. A method as claimed in any preceding claim, wherein: The polyether monol is selected from the monomethyl ether of poly(propylene oxide) glycol.

11. A method as claimed in any preceding claim, wherein: The polyether monol has a molecular weight (Mn) of greater than 800 Da and less than 2,000 Da, more preferably less than 1,500 Da, and very particularly preferably 1,000 Da.

12. A method as claimed in any preceding claim, wherein: The polyether monol is a poly(propylene oxide) diol, particularly having a molecular weight (M) of 1,000 Da. n )'s monomethyl ether of poly(propylene glycol).

13. A method as claimed in any preceding claim, wherein: The polyisocyanates are aliphatic.

14. A method as claimed in any preceding claim, wherein: The polyisocyanate is selected from the group consisting of isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI) and mixtures of these.

15. According to any one of claims 1 to 12, wherein The polyisocyanate is a mixture of 2,4'-MDI and 4,4'-MDI.

16. According to any one of claims 1 to 12, wherein The polyisocyanate is a mixture of 2,4'-MDI and 4,4'-MDI, wherein the weight ratio of 2,4'-MDI to 4,4'-MDI is 0.667-1.5, more preferably 0.8-1.5, and most preferably 1-1.

5.

17. According to any one of claims 1 to 12, wherein The polyisocyanate used to make the prepolymer is a mixture of 4,4'-MDI and 2,4-MDI, wherein the weight ratio of 4,4'-MDI to 2,4-MDI is 1:

1.

18. A method as claimed in any preceding claim, wherein: The at least one polyisocyanate is used in a stoichiometric excess of 2 to 15 times relative to the monol, more preferably 8 to 12 times relative to the monol, particularly preferably 10 times relative to the monol.

19. A method as claimed in any preceding claim, wherein: The prepolymer is made by reacting poly(propylene glycol) monomethyl ether with a mixture of 2,4'-MDI and 4,4'-MDI.

20. A method as claimed in any preceding claim, wherein: The prepolymer is prepared by making the molecular weight (M n )800-1,500Da poly(propylene glycol) monomethyl ether is reacted with a mixture of 2,4'-MDI and 4,4'-MDI.

21. A method as claimed in any preceding claim, wherein: The at least one polyether monol is used in component A in an amount of 5-20 wt %, more preferably 6-10 wt %, particularly preferably 8-9 wt %, based on the total weight of component A.

22. A method as claimed in any preceding claim, wherein: The at least one polyisocyanate is used in component A in an amount of 5 to 20 wt %, based on the total weight of component A, more preferably 6 to 15 wt %, very particularly preferably 10 to 11 wt %.

23. A method as claimed in any preceding claim, wherein: The NCO-terminated prepolymer comprises 30 to 55 wt %, more preferably 35 to 50 wt %, particularly preferably 42 to 45 wt %, of polyether monool, based on the total weight of the prepolymer.

24. A method as claimed in any preceding claim, wherein: The NCO-terminated prepolymer comprises 40 to 65 wt %, more preferably 45 to 60 wt %, particularly preferably 50 to 58 wt %, of diisocyanate, based on the total weight of the prepolymer.

25. A method as claimed in any preceding claim, wherein: The prepolymer comprises 30-55 wt %, more preferably 35-50 wt %, particularly preferably 42-45 wt % of polyether monool, based on the total weight of the prepolymer, and 40-65 wt %, more preferably 45-60 wt %, particularly preferably 50-58 wt % of diisocyanate, based on the total weight of the prepolymer.

26. A method as claimed in any preceding claim, wherein: The prepolymer is used in component A in an amount of 15 to 30 wt %, based on the total weight of component A, more preferably 16 to 25 wt %, very particularly preferably 18 to 20 wt %.

27. A method as claimed in any preceding claim, wherein: Component A and / or component B additionally comprises a silane comprising a silane covalently bonded to C 8-20 A hydrolyzable silylalkoxy group of an alkyl group.

28. A method as claimed in any preceding claim, wherein: Component A and / or component B comprises hexadecyltrimethoxysilane.

29. A method as claimed in any preceding claim, wherein: Component A and / or component B contains silane in an amount of 0.25-3 wt %, more preferably 0.5-2 wt %, particularly preferably 0.75-1.2 wt %, based on the total weight of component A or component B.

30. A method as claimed in any preceding claim, wherein: Component A and / or component B additionally comprises a fibrous filler, such as wollastonite.

31. Any preceding claim, wherein: Component A and / or component B comprises wollastonite in an amount of 0.5-4 wt %, based on the total weight of component A or component B, more preferably 1-3 wt %, very particularly preferably 1.7-2.2 wt %.

32. A method as claimed in any preceding claim, wherein: The at least one polyol comprises a polyol having a molecular weight less than 1,500 Da, more preferably less than or equal to 1,000 Da.

33. A method as claimed in any preceding claim, wherein: The at least one polyol includes diols, triols and mixtures of these.

34. A method as claimed in any preceding claim, wherein: The at least one polyol comprises at least one diol, in particular a polyether-based diol.

35. A method as claimed in any preceding claim, wherein: The at least one polyol comprises a poly(propylene oxide)-based diol.

36. A method as claimed in any preceding claim, wherein: The at least one polyol comprises a mixture of diols and triols.

37. Any preceding claim, wherein: The at least one polyol includes diols, triols and mixtures of these, all of which have a molecular weight of less than 1,500 Da, more preferably less than 1,000 Da.

38. A method as claimed in any preceding claim, wherein: The at least one polyol comprises a mixture of diols and triols having a molecular weight of less than 1,500 Da, more preferably less than 1,000 Da.

39. Any preceding claim, wherein: The at least one polyol comprises a polyether polyol.

40. Any preceding claim, wherein: The at least one polyol comprises a polyether polyol selected from the group consisting of: poly(C 2-4 [0043] Polyols based on poly(ethylene oxide), polyols based on poly(propylene oxide), polyols based on poly(butylene oxide) and mixtures of these.

41. Any preceding claim, wherein: The at least one polyol is selected from poly(propylene oxide) based polyols.

42. Any preceding claim, wherein: The at least one polyol comprises a triol.

43. Any preceding claim, wherein: The at least one polyol comprises a polyol selected from the group consisting of poly(C 2-4 -alkylene oxide) triol.

44. Any preceding claim, wherein: The at least one polyol comprises a poly(propylene oxide)-based triol.

45. Any preceding claim, wherein: The at least one polyol includes castor oil.

46. ​​Any preceding claim, wherein: The at least one polyol includes a mixture of polyether glycol and castor oil.

47. Any preceding claim, wherein: The at least one polyol comprises a mixture of a polyether glycol having a molecular weight of less than 600 Da and castor oil.

48. Any preceding claim, wherein: The at least one polyol comprises a mixture of a poly(propylene oxide)-based glycol and castor oil.

49. Any preceding claim, wherein: The at least one polyol comprises a mixture of a poly(propylene oxide)-based glycol having a molecular weight of less than 600 Da and castor oil.

50. Any preceding claim, wherein: Component B comprises 2 to 15 wt %, based on the total weight of component B, more preferably 4 to 10 wt %, very particularly preferably 5 to 7 wt %, of diol.

51. Any preceding claim, wherein: Component B comprises 5 to 20 wt %, more preferably 7 to 15 wt %, particularly preferably 8 to 11 wt %, of triol, based on the total weight of component B.

52. Any preceding claim, wherein: Component B comprises 2 to 15 wt %, more preferably 4 to 10 wt %, very particularly preferably 5 to 7 wt %, based on the total weight of component B, of diols having a molecular weight of less than 600 Da.

53. Any preceding claim, wherein: Component B comprises, based on the total weight of component B, 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-11 wt % of a triol having a molecular weight of less than 1,000 Da.

54. Any preceding claim, wherein: Component B comprises 2-15 wt %, more preferably 4-10 wt %, more particularly preferably 5-7 wt %, based on the total weight of component B, of a diol having a molecular weight of less than 600 Da, and 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-11 wt %, based on the total weight of component B, of a triol having a molecular weight of less than 1,000 Da.

55. Any preceding claim, wherein: Component B comprises 4 to 10 wt %, very particularly preferably 5 to 7 wt %, based on the total weight of component B, of poly(propylene oxide) diol having a molecular weight of less than 600 Da.

56. Any preceding claim, wherein: Component B comprises 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-11 wt %, of castor oil, based on the total weight of component B.

57. Any preceding claim, wherein: Component B comprises 4-10 wt %, more particularly preferably 5-7 wt %, based on the total weight of component B, of poly(propylene oxide) diol having a molecular weight of less than 600 Da, and 5-20 wt %, more particularly 7-15 wt %, particularly preferably 8-11 wt %, based on the total weight of component B, of castor oil.

58. Any preceding claim, wherein: The catalyst is selected from tertiary amine catalysts and organic metal catalysts.

59. Any preceding claim, wherein: The catalyst is selected from alkyltin carboxylates, alkyltin oxides and tin mercaptides.

60. Any preceding claim, wherein: The catalyst is dioctyltin mercaptan.

61. Any preceding claim, wherein: The catalyst is used in an amount of 0.0005 to 0.002 wt %, based on the total weight of component B, more preferably 0.00075 to 0.0015 wt %.

62. Any preceding claim, wherein: The catalyst is dioctyltin mercaptan used in an amount of 0.0005 to 0.002 wt %, based on the total weight of component B, more preferably 0.00075 to 0.0015 wt %.

63. Any preceding claim, wherein: Component B additionally comprises polyesterdiols.

64. Any preceding claim, wherein: Component B additionally comprises polycaprolactone.

65. Any preceding claim, wherein: Component B additionally comprises a molecule having an average molecular weight (M) of 1,500-2,500 Da, more preferably 2,000 Da. n ) of polycaprolactone.

66. Any preceding claim, wherein: Component B additionally comprises polyester diols used in an amount of 0.1 to 0.4 wt %, based on the total weight of component B, more preferably 0.15 to 0.25 wt %.

67. Any preceding claim, wherein: The ATH has a multimodal particle size distribution.

68. Any preceding claim, wherein: The ATH has a bimodal particle size distribution.

69. Any preceding claim, wherein: The aluminum hydroxide has the following particle size distribution: D 10 =0.5μm D 50 =8μm D 90 =80μm。 70. Any preceding claim, wherein: ATH is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form an adhesive mixture, the concentration of ATH in the adhesive mixture is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of the adhesive mixture.

71. Any preceding claim, wherein: ATH is present in component A, component B, or both.

72. Any preceding claim, wherein: Both component A and component B contain ATH.

73. Any preceding claim, wherein: The concentration of ATH in component A is 40-65 wt %, more preferably 43-60 wt %, particularly preferably 44-57 wt %, based on the total weight of component A.

74. Any preceding claim, wherein: The concentration of ATH in component B is 40-65 wt %, based on the total weight of component B, more preferably 43-60 wt %, particularly preferably 44-57 wt %.

75. Any preceding claim, wherein: The concentration of ATH in component A is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of component A, and the concentration of ATH in component B is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of component B.

76. Any preceding claim, wherein: The aluminum oxide has spherical particles.

77. Any preceding claim, wherein: The alumina particles have an aspect ratio of 0.8-1.2, more preferably 0.9-1.

1.

78. Any preceding claim, wherein: The alumina has a multimodal particle size distribution.

79. Any preceding claim, wherein: The alumina is bimodal.

80. Any preceding claim, wherein: The aluminum oxide has the following particle size distribution: D 10 =1-5μm, preferably 3μm D 50 =45-50μm, preferably 46.5μm D 90 =80-100 μm, preferably 90 μm.

81. Any preceding claim, wherein: The aluminum oxide has the following particle size distribution:

82. Any preceding claim, wherein: The aluminum oxide has a D of 5.7 μm. 50 of aluminum oxide and has a D of 72 μm 50 A mixture of aluminum oxide.

83. Any preceding claim, wherein: The aluminum oxide has a D of 5.7 μm. 50 of aluminum oxide and has a D of 72 μm 50 A mixture of 0.4:1 to 0.8:1, more preferably 0.5:1 to 0.7:1, particularly preferably 0.6:1 (wt:wt) of aluminum oxide.

84. Any preceding claim, wherein: The aluminum oxide is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form a binder mixture, the concentration of aluminum oxide in the binder mixture is 15-40 wt%, more preferably 16-35 wt%, particularly preferably 17-34 wt%, based on the total weight of the binder mixture.

85. Any preceding claim, wherein: The aluminum oxide is present in component A, component B, or both.

86. Any preceding claim, wherein: Both component A and component B contain aluminum oxide.

87. Any preceding claim, wherein: The concentration of aluminum oxide in component A and / or B is 15-40 wt %, based on the total weight of component A or B, more preferably 16-35 wt %, particularly preferably 17-34 wt %.

88. Any preceding claim, wherein: The ATH and the alumina are multimodal.

89. Any preceding claim, wherein: The ATH and the alumina are bimodal.

90. Any preceding claim, wherein: The ATH and the alumina are multimodal, and the alumina has a spherical particle shape.

91. Any preceding claim, wherein: The ATH and the alumina are multimodal and the alumina has an aspect ratio of 0.8-1.2, more preferably 0.9-1.

1.

92. Any preceding claim, wherein: The ATH and the alumina are bimodal, and the alumina has a spherical particle shape.

93. Any preceding claim, wherein: The ATH and the alumina are bimodal, and the alumina has an aspect ratio of 0.8-1.2, more preferably 0.9-1.

1.

94. Any preceding claim, wherein: The ATH has the following particle size distribution: D 10 =0.5μm D 50 =8μm D 90 =80μm, And the aluminum oxide has the following particle size distribution: D 10 =1-5μm, preferably 3μm D 50 =45-50μm, preferably 46.5μm D 90 =80-100 μm, preferably 90 μm.

95. Any preceding claim, wherein: The ATH is present in component A and / or component B such that when the two components are mixed (preferably in a volume ratio of 0.8:1 to 1.2:1, more preferably 1:1) to form a binder mixture, the concentration of ATH in the binder mixture is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of the binder mixture, and the concentration of aluminum oxide in the binder mixture is 15-40 wt%, more preferably 16-35 wt%, particularly preferably 17-34 wt%, based on the total weight of the binder mixture.

96. Any preceding claim, wherein: ATH and alumina are present in both component A and component B.

97. Any preceding claim, wherein: The concentration of ATH in component A is 40-65wt%, more preferably 43-60wt%, particularly preferably 44-57wt%, based on the total weight of component A, and the concentration of aluminum oxide in component A is 15-40wt%, more preferably 16-35wt%, particularly preferably 17-34wt%, based on the total weight of component A.

98. Any preceding claim, wherein: The concentration of ATH in component B is 40-65 wt%, more preferably 43-60 wt%, particularly preferably 44-57 wt%, based on the total weight of component B, and the concentration of aluminum oxide in component B is 15-40 wt%, more preferably 16-35 wt%, particularly preferably 17-34 wt%, based on the total weight of component B.

99. Any preceding claim, wherein: The concentration of ATH in component A is 40-65wt%, more preferably 43-60wt%, particularly preferably 44-57wt%, based on the total weight of component A, and the concentration of ATH in component B is 40-65wt%, more preferably 43-60wt%, particularly preferably 44-57wt%, based on the total weight of component B, and the concentration of aluminum oxide in component A is 15-40wt%, more preferably 16-35wt%, particularly preferably 17-34wt%, based on the total weight of component A, and the concentration of aluminum oxide in component B is 15-40wt%, more preferably 16-35wt%, particularly preferably 17-34wt%, based on the total weight of component B.

100. Any preceding claim, wherein: Component A and component B are mixed in a volume ratio of A:B of 0.8-1.

2.

101. Any preceding claim, wherein: Component A and component B are mixed in a volume ratio of A:B of 1.

102. Any preceding claim, wherein: As described in the examples, the adhesive shows a thermal conductivity of 1.5 W / mK or more, more preferably 1.6 W / mK or more, more particularly preferably 1.8 W / mK or more after curing for seven days at 23° C. and 50% relative humidity when measured according to ASTM 5470.

103. Any preceding claim, wherein: When according to DIN EN 1465, the bonding area is: 250mm 2 (10 x 25 mm), an adhesive layer thickness of 1 mm, the adhesive showed a lap shear strength of 1.5 MPa or greater after curing for seven days at 23°C and 50% relative humidity when measured using electro-coated steel for both substrates.

104. Any preceding claim, wherein: The adhesive mixture resulting from mixing component A and component B has a working time of greater than 35 minutes, more preferably greater than 40 minutes, and particularly preferably greater than 50 minutes, wherein the working time is the time for generating a compressive force of 150 kPa when pressed into a 1 mm gap by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min.

105. Any preceding claim, wherein: The adhesive mixture resulting from mixing Part A and Part B has a compression force of less than 80 KPa, more preferably less than 78 KPa immediately after mixing when pressed by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min into a 1 mm gap.

106. Any preceding claim, wherein: The adhesive mixture resulting from mixing Part A and Part B has a compression force of less than 130 KPa, more preferably less than 128 KPa 30 minutes after mixing when pressed by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min into a 1 mm gap.

107. Any preceding claim, wherein: The adhesive mixture resulting from mixing Part A and Part B has a compression force of less than 160 KPa, more preferably less than 155 KPa 60 minutes after mixing when pressed by parallel plates having a diameter of 50 mm at a pressing rate of 62.5 mm / min into a 1 mm gap.